Combination Treatment with Gua Sha and Blood-letting Causes Attenuation of Systemic Inflammation, Activated Coagulation, Tissue Ischemia and Injury during Heatstroke in Rats - 屠文展 程瑞动 胡洁 王杰枝 林海燕 邹恩苗 王万胜 楼新法 蒋松鹤 (Chinese journal of integrative medicine, 2015)
Objective： Gua Sha and Blood-letting at the acupoints were Chinese traditional therapies for heatstroke. The purpose of present study was to assess the therapeutic effect of Gua Sha on the DU Meridian and Bladder Meridian combined with Blood-letting acupoints at Shixuan （EX-UE 11） and Weizhong （BL 40） on heatstroke. Methods： Anesthetized rats, immediately after the onset of heatstroke, were divided into four major groups： Gua Sha group, Blood-letting group, Gua Sha combined with Blood-letting group and model group. They were exposed to ambient temperature of 43℃ to induce heatstroke. Another group of rats were exposed to room temperature （26℃） and used as normal control group. Their survival times were measured. In addition, their physiological and biochemical parameters were continuously monitored. Results： When rats underwent heatstroke, their survival time values were found to be 21-25 min. Treatment of Gua Sha combined with Blood- letting greatly improved the survival time （230 ± 22 rain） during heatstroke. All heatstoke animals displayed and activated coagulation evidenced by increased prothrombin time （PT）, activated partial thromboplastin time （aPTT）, D-dimer, and decreased platelet count, protein C. Furthermore, the animals displayed systemic inflammation evidenced by increased the serum levels of cytokines interleukin-1β （IL-1β）, tumor necrosis factor α （TNF-α） and malondialdehyde （MDA）. Biochemical markers evidenced by cellular ischemia and injury/dysfunction included increased plasma levels of blood urea nitrogen （BUN）, creatinine, serum glutamic oxaloacetic transaminase （SGOT）, serum glutamic pyruvic transaminase （SGPT）, and alkaline phosphatase （ALP） were all elevated during heatstroke. Core temperatures （Tco） were also increased during heatstroke. In contrast, the values of mean arterial pressure were significantly lower during heatstroke. These heatstroke reactions were all significantly suppressed by treatment of Gua Sha and Blood-letting, especially the combination therapy. Conclusion： Gua Sha combined with Blood-letting after heatstroke may improve survival by ameliorating systemic inflammation, hypercoagulable state, and tissue ischemia and injury in multiple organs.